Double Chooz neutrino detector: neutron detection systematic errors and detector seasonal stability - Chang, Pi-Jung (Kansas State University, 2013)
In March 2012, the Double Chooz reactor neutrino experiment published its most precise result so far: sin[superscript]2 2theta13 = 0.109 +/- 0.030(stat.) +/- 0.025(syst.). The statistical significance is 99.8% away from the no-oscillation hypothesis. The systematic uncertainties from background and detection efficiency are smaller than the first publication of the Double Chooz experiment. The neutron detection efficiency, one of the biggest contributions in detection systematic uncertainties, is a primary topic of this dissertation. The neutron detection efficiency is the product of three factors: the Gd-capture fraction, the efficiency of time difference between prompt and delayed signals, and the efficiency of energy containment. [superscript]252 Cf is used to determine the three factors in this study. The neutron detection efficiency from the [superscript]252 Cf result is confirmed by the electron antineutrino data and Monte Carlo simulations. The systematic uncertainty from the neutron detection efficiency is 0.91% used in the sin[superscript]2 2theta13 analysis. The seasonal variation in detector performance and the seasonal variations of the muon intensity are described in detail as well. The detector stability is confirmed by observation of two phenomena: 1) the [electron antineutrino] rate, which is seen to be uncorrelated with the liquid scintillator temperature, and 2) the daily muon rate, which has the expected correspondence with the effective atmospheric temperature. The correlation between the muon rate and effective atmospheric temperature is further analyzed in this thesis to determine the ratio of kaon to pion in the local atmosphere. An upper limit on instability of the neutron detection efficiency is established in the final chapter. The systematic error, 0.13%, from the relative instability is the deviation of the calibration runs. This thesis concludes with the potential systematic errors of neutron detection efficiency and estimation of how these potential systematic errors affect the result of sin[superscript]2 2theta13.
Keywords: Neutrino; Gadolinium; Neutron; Neutrino oscillation; Double Chooz; Particle Physics (0798)